Orodental manifestations in cases with partial agenesis of corpus callosum-rare phenomena - Annette M. Bhambal; Ajay Bhambal; Preeti Nair; Sheela S. Bhambal (Elsevier, 2015)
This article focuses on the associated signs and symptoms of patients with partial agenesis of the corpus callosum. The orodental manifestations of such cases have been given special weightage which will prove to be of great help to oral physician when encountered with such cases. Case details: Two siblings, aged 14 and 16 years, reported with a chief complaint of severe crowding of teeth with mouth breathing habit. They were low birth-weight babies and had been born to non-consanguinous parents. The distinguishing features of these children were craniofacial abnormalities, delayed developmental milestones, mild mental retardation and abnormal gait. The nosological features and the clinical manifestations of this syndrome and the plausible autosomal recessive inheritance of this rare syndrome have been elicited. The diagnosis was based on characteristic phenotype, in particular striking craniofacial and skeletal abnormalities and neuroimaging. Conclusion: It is a challenge for healthcare professionals to help these youths to maximize their potential as human beings and help them achieve a meaningful adulthood. On the other hand, diagnosing such cases can be a challenge to dentistry. A systematic protocol, if adhered, can lead to a more appropriate diagnosis. Managing such cases in a clinical setup involves a multispeciality and interdisciplinary approach.